Carbon monoxide poisoning: beyond survival - mortality, morbidities, and risk factors, a Turkey sample - Erdoğan Öz; Osman Küçükkelepçe; Osman Kurt; Aşkı Vural (PeerJ, 2023)
Background We aimed to investigate the effect of poisoning on mortality leading to new morbidities in people who survived the poisoning. Methods The descriptive-retrospective study evaluated all carbon monoxide poisoning cases between 2012 and 2022 in the Adiyaman. For the fatality, all cases were followed up through Turkey’s death notification system until the end of 2022. One-year health records of cases treated as inpatients in Adiyaman hospitals were analyzed for nine diagnoses. A total of 4,395 carbon monoxide cases, recorded over 11 years, were all noted to be accidental cases. Results The rate of carbon monoxide poisoning in Adıyaman was calculated as 63.2 per hundred thousand. A total of 87 (2%) of the cases died. The population’s hospitalization rate was 1.71, while the mortality rate was 1.25 in a hundred thousand. Among the cases, the hospitalization rate was 2.7, and the admission to intensive care rate was 1.7. The fatality rate was 6.5% for those hospitalized and 12.2% for those admitted to the intensive care unit. The highest fatality rate was 65.5% in patients aged 65 and above. One out of five morbidities was developed in 8.4% of cases within one year. The fatality rate of those who developed morbidities (40%) was higher than those who did not (5.5%). Being male posed a 1,886-fold risk for mortality, and each increase in age posed a 1,086-fold risk for mortality. Conclusion Individuals who had carbon monoxide poisoning should be followed up closely for one year after poisoning due to the possibility of the emergence of new morbidities that increase the risk of mortality.